Environmental and Management Factors that Influence Commelina Species in Selected Agro-Ecological Zones in Western Kenya - Runyambo, Irakiza; Andika, Darius; Watako, Arnold; Mwonga, Samuel; Musili, Paul; Kirika, Paul (merican Journal of Plant Sciences, 2022)
Commelina species are plant resources full of promise as future food and feed that thrive in diverse ecosystems. They are medicinal plants, leafy vegetables, forage for ruminants, feed for cricket insects, crop protection, and fuel. However, information regarding factors driving Commelina in agro-ecological zones in Western Kenya is lacking. Therefore, we investigated the diversity of Commelina species, the composition of associated weed species as well as environmental and management factors affecting their diversity and distribution based on 22 variables from 12 production sites. In the survey, 115 species belonging to 30 families were recorded of which 11 Commelina species were identified. Among Commelina species, Commelina diffusa and Commelina benghalensis var. benghalensis (non-hybrid variant) had higher relative density. Multiple linear regressions revealed that the environment (exchangeable sodium percentage, magnesium, soil pH, and total nitrogen) and management (agriculture system type) variables exert a stronger effect on the diversity of Commelina species. Detrended Correspondence Analysis detected different ecological conditions for Commelina species and the composition of associated weed species. The forward selection based on Canonical Correspon-dence Analysis indicated that the distribution of Commelina species responded significantly to soil pH,available phosphorous, total nitrogen, fertility, and crop spacing. Partitioning variation showed the great importance to the environment than management (10.57% versus 5.97%). The low shared variance (environment × management) was −0.4%, indicating that the two factors have a more individualistic than interactive nature. However, the 83.86% that remained unexplained was attributed to stochastic variation or unmeasured variables. This study suggests that the identified five important variables affecting the distribution of Commelina species will certainly contribute to the prioritization of ecological aspects leading to the growth condition of Commelina species.
Keywords: Commelina; Canonical Correspondence Analysis (CCA); Environment; Management; Weed Vegetation